2019
DOI: 10.1097/ncm.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Excellence in Population Health

Abstract: Purpose/Objective: The Community-based Care Transitions Program (CCTP) defined a broad spectrum of interventions and services for elderly patients at high risk of hospital readmission. The purposes for a CCTP as developed by the Centers for Medicare & Medicaid Services are to improve transitions of beneficiaries from the inpatient hospital setting to other care settings, to improve quality of care, to reduce readmissions for high-risk beneficiaries, and to document measurable savings. The goals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Table 2 summarizes the 11 articles that included partnerships focused on improving care coordination/transitions. Eight of these studies used case study designs to provide descriptions of partnerships with diverse organizations to support coordination of care for high-risk populations (e.g., Medicare, Medicaid; Baxter et al, 2018; Berkowitz et al, 2016; Everett et al, 2014; Hsiao et al, 2018; Malseptic et al, 2018; Sandberg et al, 2014; Sherry et al, 2016; Warren et al, 2019). Findings suggested that multisector partnerships are helpful in removing barriers to engagement with patients and connecting them to needed clinical, behavioral, and community-based services (Baxter et al, 2018; Berkowitz et al, 2016; Everett et al, 2014; Hsiao et al, 2018; Malseptic et al, 2018; Sandberg et al, 2014; Warren et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes the 11 articles that included partnerships focused on improving care coordination/transitions. Eight of these studies used case study designs to provide descriptions of partnerships with diverse organizations to support coordination of care for high-risk populations (e.g., Medicare, Medicaid; Baxter et al, 2018; Berkowitz et al, 2016; Everett et al, 2014; Hsiao et al, 2018; Malseptic et al, 2018; Sandberg et al, 2014; Sherry et al, 2016; Warren et al, 2019). Findings suggested that multisector partnerships are helpful in removing barriers to engagement with patients and connecting them to needed clinical, behavioral, and community-based services (Baxter et al, 2018; Berkowitz et al, 2016; Everett et al, 2014; Hsiao et al, 2018; Malseptic et al, 2018; Sandberg et al, 2014; Warren et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Eight of these studies used case study designs to provide descriptions of partnerships with diverse organizations to support coordination of care for high-risk populations (e.g., Medicare, Medicaid; Baxter et al, 2018; Berkowitz et al, 2016; Everett et al, 2014; Hsiao et al, 2018; Malseptic et al, 2018; Sandberg et al, 2014; Sherry et al, 2016; Warren et al, 2019). Findings suggested that multisector partnerships are helpful in removing barriers to engagement with patients and connecting them to needed clinical, behavioral, and community-based services (Baxter et al, 2018; Berkowitz et al, 2016; Everett et al, 2014; Hsiao et al, 2018; Malseptic et al, 2018; Sandberg et al, 2014; Warren et al, 2019). Additional key takeaways documented across these studies included a need for better integration of providers across the continuum of care (Berkowitz et al, 2016; Everett et al, 2014; Hsiao et al, 2018; Malseptic et al, 2018; Sherry et al, 2016) and the use of available data and information technology to support better information sharing and design interventions tailored to communities of interest (Berkowitz et al, 2016; Hsiao et al, 2018; Malseptic et al, 2018; Sherry et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Orchestrating cooperation among health workers increases patient satisfaction [ 50 ] and reduces length of hospital stay [ 51 ]. If we can ensure that older adult patients are satisfied with their care, we may reap the rewards of fewer avoidable visits to the ED [ 52 ]. The benefits of a successful care transition are not limited to individual patients as they impact on communities and caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…2 Older adults with cardiovascular disease benefit greatly from cardiac rehabilitation 3 ; however, transitions from one health care setting to another can result in patient vulnerability, often aggravated by lack of coordination among healthcare providers and unclear discharge instructions. 4…”
Section: Introductionmentioning
confidence: 99%
“…2 Older adults with cardiovascular disease benefit greatly from cardiac rehabilitation 3 ; however, transitions from one health care setting to another can result in patient vulnerability, often aggravated by lack of coordination among healthcare providers and unclear discharge instructions. 4 Transitional care is a set of actions that ensure the coordination and continuity of healthcare as individuals transfer between different locations or levels of care. 5 Care transitions can be very challenging because they encompass the integration and coordination of care across different health care sectors and providers that are involved in the patient's circle of care.…”
Section: Introductionmentioning
confidence: 99%